New Polylactic Acid Composites Reinforced with Artichoke Fibers - Botta, Luigi (Materials (Basel), 2015)
In this work, artichoke fibers were used for the first time to prepare poly(lactic acid) (PLA)-based biocomposites. In particular, two PLA/artichoke composites with the same fiber loading (10% w/w) were prepared by the film-stacking method: the first one (UNID) reinforced with unidirectional long artichoke fibers, the second one (RANDOM) reinforced by randomly-oriented long artichoke fibers. Both composites were mechanically characterized in tensile mode by quasi-static and dynamic mechanical tests. The morphology of the fracture surfaces was analyzed through scanning electron microscopy (SEM). Moreover, a theoretical model, i.e., Hill’s method, was used to fit the experimental Young’s modulus of the biocomposites. The quasi-static tensile tests revealed that the modulus of UNID composites is significantly higher than that of the neat PLA (i.e., ~40%). Moreover, the tensile strength is slightly higher than that of the neat matrix. The other way around, the stiffness of RANDOM composites is not significantly improved, and the tensile strength decreases in comparison to the neat PLA.